Model of Estimating the Aquaculture Carrying Capacity for Shallow-Water Tidal Embayments; Model Application to Ben Beo bay, Cat Ba Island, Hai Phong - Thi Le Ha, Trinh (VNU Journal of Science: Earth and Environmental Sciences, 2018)
Abstracts: Model was developed to estimate the production carrying capacity of water bodies based on nutrient inputs from aquacultures, flushing rates and the risk of algal blooms for Shallow-Water Tidal Embayments. Model was applied to Ben Beo bay, Cat Ba Island, Hai Phong. The results suggest that nutrient loadings from cage-culture practices in 2017 were greater than the carrying capacity of Ben Beo during low and average tidal exchange. The emission of nutrients by fish cultures in 2008 into water body was greater than the sustainable carrying capacity. The aquaculture production in Plan has not overcome Ben Beo’s carrying capacity even during low tidal exchange. However, during neap tide, carrying capacity has been able to overcome. Keywords: Carrying capacity, nutrient, aquacultures. References: [1] Số liệu quan trắc hàng năm khu vực biển quanh đảo Cát Bà do Trung tâm quan trắc môi trường Biển, Viện Hải sản thực hiện. [2] Sở VHTTDL Hải phòng (2010), Báo cáo: Quy hoạch tổng thể phát triển du lịch bền vững quần đảo Cát Bà đến năm 2025, tầm nhìn đến năm 2050. [3] UBND huyện Cát Hải (2008). Báo cáo đánh giá thực trạng phát triển nuôi cá lồng bè trên vịnh Cát Bà, Hải Phòng. [4] Sở Nông nghiệp và Phát triển nông thôn Hải Phòng (2010), Đề án: Quy hoạch chi tiết phát triển nuôi trồng hải sản trên vùng biển Hải Phòng đến năm 2015, định hướng đến năm 2020. [5] Legović Tarzan; Palerud Rune; Christensen Guttorm; White Patrick; Regpala, Regie (2008), A model to estimate aquaculture carrying capacity in three areas of the Philippines, Science Diliman (0115-7809) Vol. 20, p.31-40. [6] Trịnh Thị Lê Hà, Đoàn Văn Bộ (2016), Ước tính lượng phát thải dinh dưỡng từ hoạt động nuôi cá lồng tại vịnh Bến Bèo, Cát Bà, Hải Phòng, Tạp chí Khoa học ĐHQGHN: Các Khoa học Trái đất và Môi trường, Tập 32, Số 3S , tr. 77-82. [7] Hoyer M. V.; Frazer T. K.; Notestein S. K.; Canfield D. E. (2002), Nutrient, chlorophyll, and water clarity relationships in Florida’s nearshore coastal waters with comparisons to freshwater lakes, Canada Journal of Fisheries and Aquatic Sciences 59, p. 1024-1031. [8] Tổng cục Biển và Hải đảo Việt Nam, Trung tâm Hải văn, Bảng thủy triều 2016, 2017, 2018, tập 1, Nhà xuất bản khoa học tự nhiên và công nghệ.